Research Designs and Literature in the Field of Visual Impairment: What Informs Our Practices?. (September 2020) - Sutter, Chevonne; Demchak, MaryAnn; Grumstrup, Brianna; Forsyth, Andrea; Grattan, Jill
Introduction: This descriptive study identified types of articles published and research designs used in targeted special education journals. Articles in visual impairment (i.e., low vision or blindness) published between 2012 and 2017 were examined to determine what literature informed the field during the 6-year period. Method: A total of 4, 850 articles from 37 journals were reviewed. Initially, all articles published from 2012 through 2014 in targeted disability journals across categories related to the Individuals with Disabilities Education Act (IDEA) were reviewed. Subsequently, articles published from 2015 through 2017 in six key journals in visual impairment and deafblindness were reviewed. Each article in every volume of selected journals in the 6-year period was coded for type, research design, and target population. Results: The majority of research designs implemented with IDEA-eligible individuals with visual impairments were quantitative, specifically regression analyses, comparative, and single-case research designs (hereafter, single-case designs). Studies targeting non-IDEA eligible participants nearly doubled those targeting children with visual impairments. Less than one third of studies identified were intervention studies. Single-case designs were the most commonly used designs for intervention studies, and few reported effect size. The overall small number of studies with children with visual impairments indicate an increased need for experimental studies to identify evidence-based practices. Discussion: A greater number of empirical than nonempirical articles was identified in visual impairment, possibly indicating increased investigation of practices and interventions. This trend aligns with the current focus on using evidence and data to support practice and policy. Further research should evaluate quality of studies. Implications for practitioners: It is important to be familiar with the body of research informing the field of visual impairment to understand the evidence underlying its practices and policies. It is recommended that increased numbers of high-quality intervention studies be conducted to identify evidence-based practices.